POTENSI BAHAN GALIAN PASIR KUARSA DI KECAMATAN LABUHAN MARINGGAI, KABUPATEN LAMPUNG TIMUR, PROVINSI LAMPUNG - -, Agung Mulyo (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
District of Labuhan Maringgai, Sub-Province East Lampung, Lampung, richly of quartz-sand. Potency, amount of reserve, quality of every type of quartz-sand is important to know. Mapping of natural resources specially quartz-sand is required for development program of Lampung area, especially related to invesment and promotion in mining.Almost of all region of Labuhan Maringgai District consist of quartz-sand. Quartz-sand which good quality (Sio2 > 95 %) there are in Sukorahayu (1.768.000 m3), Sriminosari (1.006.500 m3), Karya Makmur (1.320.000 m3), and Karya Tani (3.082.000 m3).